Providing Emergency Medical Care at the Prehospital Stage to Patients With Acute Myocardial Infarction and Acute Ischemic Stroke in Moscow: the Role of the Aviation Medical Teams of the Emergency Medical Care Center (Territorial Center of Disaster Medicine) - S. A. Gumenyuk; A. M. Shchikota; I. V. Pogonchenkova (Неотложная медицинская помощь)
The increase in the number of patients with complications of cardiovascular diseases and the need for early diagnosis of such complications and the early initiation of treatment already at the prehospital stage leads to an increasing  need for more frequent use of helicopter medical equipment, as well as for equipping aviation medical teams with highly qualified specialists. The  formation of a network of vascular invasive centers in the Moscow region,  modern equipment and its use in air ambulance conditions require constant improvement of skills among medical workers. All this undoubtedly leads to positive results, the mortality rate from heart attacks and strokes decreases, the duration of treatment and the period of rehabilitation of patients are  reduced. It should be noted that even 10 years ago, medical helicopters were used in the elimination of medical consequences in road accidents, fires and emergencies. Today, aviation medical teams are involved in more than 50% of cases with cardiovascular diseases, which undoubtedly speaks of the  prospects for the development of medical aviation in large cities.